1988
DOI: 10.1172/jci113331
|View full text |Cite
|
Sign up to set email alerts
|

Transsulfuration in an adult with hepatic methionine adenosyltransferase deficiency.

Abstract: We investigated sulfur and methyl group metabolism in a 31-yr-old man with partial hepatic methionine adenosyltransferase (MAT) deficiency. The patient's cultured fibroblasts and erythrocytes had normal MAT activity. Hepatic S-adenosylmethionine (SAM) was slightly decreased. This clinically normal individual lives with a 20-30-fold elevation of plasma methionine (0.72 mM). He excretes in his urine methionine and L-methionine-d-sulfoxide (2.7 mmol/d), a mixed disulfide of methanethiol and a thiol bound to an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 34 publications
1
74
1
Order By: Relevance
“…or oral cysteamine is an offensive breath odor, here attributable to dimethylsulfide. A similar finding has been reported in a 31-y-old man with methionine adenosyltransferase deficiency (38).…”
Section: Discussionsupporting
confidence: 89%
“…or oral cysteamine is an offensive breath odor, here attributable to dimethylsulfide. A similar finding has been reported in a 31-y-old man with methionine adenosyltransferase deficiency (38).…”
Section: Discussionsupporting
confidence: 89%
“…MetO was also detected in the blood, plasma, and urine of children with homocysteinuria (Perry et al, 1967), but the stereochemistry of the detected MetO was not investigated. Interestingly, Gahl et al (1988) detected exclusively Met-d-O in the urine of a human with MAT1A deficiency that caused a 20-to 30-fold elevation of plasma Met (0.72 mM). Hernandez et al (2004) recently identified a novel FMO gene cluster in mice and humans.…”
Section: Resultsmentioning
confidence: 98%
“…3-MTP formation has been detected in rat and monkey tissue homogenates incubated with Met (Steele and Benevenga, 1978;Scislowski and Pickard, 1993). 3-MTP has also been detected in the urine of humans with cystathionine ␤-synthase deficiency or partial hepatic MAT1A deficiency (Gahl et al, 1988;Tangerman et al, 2000). Further metabolism of 3-MTP to yield methanethiol has been demonstrated in rats (Finkelstein and Benevenga, 1986;Scislowski and Pickard, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is concern that such limitation may be counterproductive if it further reduces synthesis of AdoMet in those with some residual MAT I/III activity. At methionine levels above 300 mmol/L, metabolites produced by transamination may give rise to the offensive body odour seen in some patients, although there is no clear evidence that this is otherwise harmful (Andria et al 2005;Gahl et al 1988;Mudd et al 1995). We therefore consider that strict limitation of dietary methionine intake is unnecessary and indeed inadvisable.…”
Section: Discussionmentioning
confidence: 99%